2017
DOI: 10.21270/archi.v6i3.1921
|View full text |Cite
|
Sign up to set email alerts
|

Reações adversas a medicamentos entre idosos institucionalizados: prevalência e fatores associados.

Abstract: ResumoIntrodução: As reações adversas a medicamentos estão relacionadas a desfechos negativos da terapia, aumentando o risco de morbidade e mortalidade. Objetivos: Sendo os idosos pacientes altamente suscetíveis a essas reações devido a vários fatores, como as alterações fisiológicas que alteram a farmacocinética e farmacodinâmica, além do alto consumo de medicamentos devido à multiplicidade e cronicidade de doenças que apresentam, é de fundamental importância estudar a ocorrência das reações adversas a medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
4
0
3
Order By: Relevance
“…Therefore, to guarantee greater safety to the population in this age group, it becomes a strategy to avoid the use of this type of medication and/or to be aware of the possibilities of adverse reactions caused by them (Lopes et al 2016). A study performed with elderly people living in long-term care facilities in four municipalities in the State of São Paulo identified that among the participants who presented some type of ADR, the majority (95.4%) used at least one PIM (de Lima et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to guarantee greater safety to the population in this age group, it becomes a strategy to avoid the use of this type of medication and/or to be aware of the possibilities of adverse reactions caused by them (Lopes et al 2016). A study performed with elderly people living in long-term care facilities in four municipalities in the State of São Paulo identified that among the participants who presented some type of ADR, the majority (95.4%) used at least one PIM (de Lima et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Although the association between age and the occurrence of adverse events has become non-significant in the final multivariate analysis model, it is important to highlight that the contribution of the present study, far beyond the discussion of adverse events in adults, points out the elderly as a target public for analysis and comprehension of adverse events to antiretroviral therapy. The elderly population is highly susceptible to medication effects, and therefore require special care, which shows that studying the occurrence of adverse events in patients from this age group is fundamental 38 . Another relevant characteristic of the present study is the inclusion of people aged 60 years or older, the age group that actually represents the elderly population 39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…Incluem-se na categoria de RAM do tipo B as reações de intolerância ao fármaco, hipersensibilidade ou idiossincráticas. Embora raras, estas RAM podem causar sérias morbidades e, em alguns casos, o óbito (LIMA et al, 2017).…”
Section: Teoricamente As Rams São Classificadas Em Duas Grandes Categorias: Reaçõesunclassified